Social Identity of English Lecturers at Islamic Universities in Central Java in Sociological Discourse - Solihah, Ni'matus; Abid, Nuskhan; Noor Sulaimansyah, Muhammad (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study examines the social identity inherent in English lecturers in Islamic universities in Central Java. This research aims to reveal how the correlation between social identity and work professionalism. The research method used is narrative inquiry. This method focuses on the narrator's story based on his life experience. The results showed that social identity cannot be separated from one's self-identity. Self-identity can be a representation of where a person comes from and participation in certain groups. The social identity of lecturers can be seen in the symbols attached to themselves, such as the way they dress, speaking style, religious practices, and others. English lecturers in Islamic universities are required to integrate Islamic values with learning, research, and community service. Social identity contributes to the professional development of lecturers to create a conducive learning environment.